Aspectos da ecologia do Cuxiú de Uta Hick, Chiropotes Utahickae (Hershkovitz, 1985), com ênfase na exploração alimentar de espécies arbóreas da ilha de germoplasma, Tucuruí-PA - VIEIRA, Tatiana Martins (Universidade Federal do Pará, 2013)
In 1985, construction of the Tucurui hydroelectric power station flooded 2400 km² of forest, creating hundreds of different sizes, fragmenting the populations of many organisms, including bearded sakis (Chiropoies spp.). The present study took place on the 129-ha Germoplasma island, which is home to a group of Chiropotes utahickae, which currently contains 23 members, studied previously by Santos (2002). The present study aimed primarily to describe certain aspect of the ecology of Uta Hick's bearded saki and to characterize the dietary exploitation of tree species. Data collection was based on monthly samples of eight days, with basic behavioural data being collected in one-minute scan samples at five-minute intervals, supplemented alternately by focal-tree and focal-fruit sampling. The principal behavioural categories were feed, travel, forage, rest and social interaction (containing several subcategories). A total of 11,277 scan sample records were collected, together with 259 focal tree samples, and 711 focal fruit samples, between March and August 2004. Overall, 50.6% of activity time was devoted to locomotion, 31.9% to feeding, 10.6% to rest, 5.4% to foraging activities, and 1.2% to social interactions. The diet consisted primarily of immature seeds (31.7%), immature mesocarp (21.2%), ripe fruit (18.3%), and flowers (14.4%). Comparisons with the results of Santos (2002) indicate a number of seasonal or longitudinal differences. The sakis exploited fruit of 0.4 to 15.3 cm in length, with seeds of between 0.1 cm and 2.3 cm. The sakis were considered to be seed predators for 74.2% of the 31 species analysed, although no significant relationship was found between predation and seed size. Also, no systematic relationship was found between the distance seeds were transported and their size, suggesting the influence of other factors, such as crown dimensions and feeding party size. Twenty years after isolation, the Germoplasma sakis appear to present typical Chiropotes behaviour patterns. Tolerance of habitat fragmentation appears to be supported by the exploitation of specific resources, such as the immature mesocarp of Inga spp. during a period of resource scarcity, and the consumption of Brazil-nut (Bertholletia excelsa) flowers. Flowers appear to be an especially important resource for the sakis of the Tucuruí reservoir (Santos, 2002; Silva, 2003). The present study constitutes an important contribution to the understanding of the species' s ecology, although it is clear that the Tucurui populations require further monitoring in order to provide more detailed information on diet, social organization, and animal-plant interactions, necessary for the development of sound conservation and management strategies.